Geometry representation to develop algebraic thinking: A recommendation for a pattern investigation in pre-algebra class - Apsari, Ratih Ayu; Putri, Ratu Ilma Indra; Sariyasa; Abels, Mieke; Prayitno, Sudi (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2020)
The present study is a part of design research in local instructional theory in a pre-algebraic lesson using the Realistic Mathematics Education (RME) approach. The article will focus on recommendations for the type of pre-algebra class that supports elementary school students’ algebraic thinking. As design research study, it followed the three steps of preliminary studies, teaching experiment and retrospective analysis. The subject of the study is 32 fifth grade students of MIN 2 Palembang during the teaching experiment phase. The data were gathered from students’ worksheets, lesson observation and interviews with the students. Data analysis was done using a constant comparative qualitative method. The results from the study indicate that pattern investigation in pre-algebra class that visualized geometrically supports the students to identify the form of the pattern and construct generalization.